ON THE ISSUE OF ANTI-CORRUPTION COMPONENT ACTIVITIES OF THE NATIONAL POLICE (Bulletin of criminological association of Ukraine, 2025)
The article analyzed the deep historical roots of corruption, dating back to the times of Ancient Rome. The activities of Transparency International were studied and the relevant Transparency International ratings were developed, which demonstrate the scale of the corruption problem in Ukraine. The main indicators of the police's activity in responding to committed corruption offenses and offenses related to corruption were determined, and statistical data were considered, indicating the effectiveness of such activities of the police. The significant potential of civil society in conducting targeted educational work with the population was emphasized. The essence of the legal education work of the police in interaction with the public in the course of preventing corruption was revealed. The latest forms of police interaction with the public in the course of carrying out legal education work aimed at preventing corruption, in particular, the implementation by police officers of community security initiatives that can be implemented in the community and solve current problems of preventing corruption; Conducting explanatory and legal education work with school students by police officers of the Educational Security Service in order to convey information about the scale and consequences of the problem of corruption in Ukraine.
Keywords: National Police of Ukraine; anti-corruption component; prevention and counteraction to corruption; security initiatives; community police officers; Educational Security Service